Who Favors Magnets and Who Favors Charters? Political Ideology, Social Purpose Politics, and School Choice in the Upper South. (May 2022) - Riel, Virginia; Mickelson, Roslyn Arlin; Smith, Stephen Samuel
School choice is an increasingly important feature of the US educational landscape. Numerous studies examine whether a particular form of school choice promotes student achievement or whether a type of school choice discourages or encourages diversity by race, ethnicity, and ability. Studies also examine attitudes toward school choice, but these studies are typically limited to the views of parents, teachers, and administrators rather than public attitudes. We contribute to this literature by studying public opinion about magnet and charter schools in five southern school districts. Using a new and unique dataset, we examine if social background characteristics, political ideology, and attitudes toward the role of public schooling, neighborhood schools, and school diversity influence citizen opinion regarding magnets and charters. We find that more educated, higher income, and older individuals do not support charters, while conservatives and Republicans do. Whites are less likely to favor magnets than other races, while the more educated are more likely to favor them. Those who believe public schools should operate for the common good support magnets, as do those who favor diverse schools. However, those who favor neighborhood schools support both charters and magnets. We interpret our findings within the context of case studies of the respective locations and suggest that public opinion studies motivate public policies regarding educational choice.